Problems and difficulties in translating American idioms with animal names in English and Uzbek (Journal of Pedagogical Inventions and Practices, 2022)
This article illustrates the main features of translating English and Uzbek idioms which are formed with animal names with the clarification of challenges and difficulties resulting in incomprehension. This article is to point out various strategies, cultural identities and differences, translation principles in both English and Uzbek languages to interpret from one to another. Additionally, the paper discusses whether idioms are translated directly or equivalents are chosen.